A multiscale perspective of water resources and ecosystem services - McDonough, Kelsey Rose (Kansas State University, 2018)
Water security is one of the greatest challenges of this century. The anthropogenic and environmental demand for water could likely outpace the freshwater availability in the future due to challenges caused by the growing world population, technological and economic advancements, and climate change. The ability to ensure adequate quantities of safe, affordable, and accessible water in the future requires innovative and interdisciplinary approaches to water management using a systems perspective across multiple spatial and temporal scales. This dissertation provides a multi-scale perspective of water resources and associated ecosystem services to understand drivers of change in surface water availability across spatiotemporal scales. The ultimate goal of this work is to advance the development of water security solutions by contributing to the current water resources and ecosystem services knowledge base.
Keywords: Water resources; Ecosystem services; Spatial; Temporal; Water security